Peningkatan Pengetahuan Masyarakat melalui Edukasi Penggunaan Dexamethasone Secara Rasional di Klinik Armina Sakti Kota Bengkulu - Lusiana Lusiana; Septi Wulandari; Annadine Zahrina Ajeqy; Rahmadannisa Dwi Amanda; Ridwan Hartadi; Elsa Nur Rahmadina; Elsi Febriyani (Jurnal PKM Manajemen Bisnis, 2026)
Inappropriate use of dexamethasone without adequate knowledge or health-professional supervision poses significant risks to the community, particularly through its informal circulation as a "miracle drug" (obat dewa) and illegal addition as an active pharmaceutical ingredient (BKO) in herbal products. A community education activity was conducted at Klinik Armina Sakti, Bengkulu City, to improve participants' understanding of dexamethasone, including its therapeutic indications, adverse effects, drug interactions, BKO contamination risks in traditional medicine, product legality verification through BPOM, and the importance of medically supervised dose tapering. The intervention employed an educational presentation followed by discussion, with knowledge assessed using a seven-item multiple-choice pre-test and post-test. Simulated data from 30 participants demonstrated a mean knowledge score increase from 34.76 before education to 80.95 after education, representing an average gain of 46.19 points. The mean normalized gain (N-Gain) was 0.692, categorized as moderate according to Hake's criterion. Before education, 27 participants were in the low knowledge category and three in the adequate category; after education, 15 participants achieved adequate knowledge and 15 achieved good knowledge, with all participants showing improvement. These simulated findings illustrate the intended structure and analysis of the article; however, they must be replaced with authentic questionnaire data, or the limitation explicitly disclosed, before manuscript submission for publication.